Chile's enduring educational segregation: A trend unchanged by different cycles of reform. (17th June 2021) - Gutiérrez, Gabriel; Carrasco, Alejandro
Abstract : Socioeconomic segregation continues to be a central issue for education systems in which market‐driven reforms have been implemented. This study analyses trends of socioeconomic segregation in Chile (1999–2018), considering a period with an absence of policies aimed at reducing segregation (1999–2007) and a later stage (2008–2015) when measures were implemented with the potential to affect the socioeconomic composition of schools. Results show that the segregation of both disadvantaged and wealthy students increased to extremely high levels during the first period, and has not shown signs of any significant decrease since then. The slight reduction observed in the second period is associated with changes regarding school fees in the private subsidised education sector rather than the selectivity status of the schools. The challenges faced in fostering greater socioeconomic integration within a market‐driven educational system are discussed in this article.